Existence of solutions of multi-term fractional differential equations with impulse effects on a half line - Liu, Yuji (Nonlinear Analysis: Modelling and Control, 2017)
A class of boundary value problem for impulsive fractional differential equation on a half line is proposed. Some results on existence of solutions of this kind of boundary value problem for impulsive multi-term fractional differential equation on a half line are established by constructing a weighted Banach space, a completely continuous operator and using a fixed point theorem in the Banach space. Some unsuitable lemmas in recent published papers are pointed out. An example is given to illustrate the efficiency of the main theorems.
Keywords: multi-term fractional differential equation; impulsive effect; fractional-order Abel differential equation; fixed point theorem